The Power of Municipal Corporations to Protect Public Health and Safety - Chester James Antieau (Washington University Law Quarterly, 1951)
Municipal regulation of streets and sidewalks is regularly authorized under state law. It must, however, survive in its particular manifestations and applications state constitutional provisions, as well as the United States Constitution, particularly the latter's due process, equal protection, and commerce clauses. There is the possibility, too, that state statutes may confer upon state commissions exclusive or paramount authority over certain particulars. So, too, states may withdraw these powers from cities and confer them upon other bodies., Many forms of conflict with state authority occur in this field.
Keywords: Municipal corporations